Genetic effects of landscape, habitat preference and demography on three co‐occurring turtle species - Reid, Brendan N.; Mladenoff, David J.; Peery, M. Zachariah (Molecular ecology, 2017)
Expanding the scope of landscape genetics beyond the level of single species can help to reveal how species traits influence responses to environmental change. Multispecies studies are particularly valuable in highly threatened taxa, such as turtles, in which the impacts of anthropogenic change are strongly influenced by interspecific differences in life history strategies, habitat preferences and mobility. We sampled approximately 1500 individuals of three co‐occurring turtle species across a gradient of habitat change (including varying loss of wetlands and agricultural conversion of upland habitats) in the Midwestern USA. We used genetic clustering and multiple regression methods to identify associations between genetic structure and permanent landscape features, past landscape composition and landscape change in each species. Two aquatic generalists (the painted turtle, Chrysemys picta, and the snapping turtle Chelydra serpentina) both exhibited population genetic structure consistent with isolation by distance, modulated by aquatic landscape features. Genetic divergence for the more terrestrial Blanding's turtle (Emydoidea blandingii), on the other hand, was not strongly associated with geographic distance or aquatic features, and Bayesian clustering analysis indicated that many Emydoidea populations were genetically isolated. Despite long generation times, all three species exhibited associations between genetic structure and postsettlement habitat change, indicating that long generation times may not be sufficient to delay genetic drift resulting from recent habitat fragmentation. The concordances in genetic structure observed between aquatic species, as well as isolation in the endangered, long‐lived Emydoidea, reinforce the need to consider both landscape composition and demographic factors in assessing differential responses to habitat change in co‐occurring species.